2022
DOI: 10.3390/su14159739
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration in Fine Aroma Cocoa Agroforestry Systems in Amazonas, Peru

Abstract: One way to mitigate climate change is by reducing atmospheric CO2 levels with the establishment of agroforestry systems (AFSs) that can capture and store atmospheric CO2. This study therefore estimated the carbon sequestration in two components, aboveground (cocoa trees, other tree species, and leaf litter) and soil, in 15 fine aroma cocoa AFSs in Amazonas, Peru. These cocoa AFSs had a minimum area of 1.5 ha and were distributed into three age groups (each group consisted of five systems or farms): young cocoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The study was conducted in the cocoa agroforestry systems of the Multiple Service Cooperative APROCAM. The cooperative is composed of 235 small cocoa producers distributed across 4 districts of the province of Bagua (Aramango, Copallín, La Peca, and Imaza), 2 districts of the province of Utcubamba (Cajaruro and El Parco), and 1 district of the province of Santa María de Nieva (Nieva) in the Amazonas region [19]. APROCAM leads cocoa exports in whole or broken beans, raw except for sowing (Tariff item: 1801001900), with an FOB of USD 428,962 for 2022 and USD 366,020 for November 2023, with Spain and Italy as its main markets [2].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in the cocoa agroforestry systems of the Multiple Service Cooperative APROCAM. The cooperative is composed of 235 small cocoa producers distributed across 4 districts of the province of Bagua (Aramango, Copallín, La Peca, and Imaza), 2 districts of the province of Utcubamba (Cajaruro and El Parco), and 1 district of the province of Santa María de Nieva (Nieva) in the Amazonas region [19]. APROCAM leads cocoa exports in whole or broken beans, raw except for sowing (Tariff item: 1801001900), with an FOB of USD 428,962 for 2022 and USD 366,020 for November 2023, with Spain and Italy as its main markets [2].…”
Section: Study Areamentioning
confidence: 99%
“…To calculate the CO 2 sequestration of the agroforestry systems in tons per hectare per year, the CO 2 values reported by Goñas et al 2022 [19] were utilized. These values were obtained from 15 cocoa agroforestry systems divided into three age strata ranging from 8 to 40 years.…”
Section: Co 2 Sequestration Of Cocoa Agroforestry Systemsmentioning
confidence: 99%
“…Consequently, Amazonas is the seventh 2 cocoa-producing region in Peru [12]. However, studies have yet to explore the diversity of trees associated with this crop within this area [13,14]. Agroforestry practices require rigorous training of producers and cooperative work for crop profitability [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have yet to explore the diversity of trees associated with this crop within this area [13,14]. Agroforestry practices require rigorous training of producers and cooperative work for crop profitability [14]. Recently, it has been observed that producers are diversifying their plots by combining various indigenous timber or fruit species and are consequently gaining complementary economic and consumption advantages from cocoa cultivation [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation